Analisis Faktor Risiko Mean Arterial Pressure (MAP) dan Indeks Massa Tubuh (IMT) terhadap Kejadian Preekelamsia di Puskesmas Pakjo Periode 2023-2024 - Nur Purnama Sari; Ramesia Ratnawati; Satra Yunola; Helni Anggraini; Elvina Indah Syafriani; Yulia Yulia (Lembaga Pengembangan Kinerja Dosen, 2025)
Preeclampsia is one of the reason main morbidity and mortality mothers and perinatal throughout the world, including Indonesia. Conducting screening early when pregnancy can identify early as well as optimization monitoring of patients. Research This aim For analyze and identify connection between Mean Arterial Pressure (MAP) and Body Mass Index (BMI) with incident Preeclampsia, as well as determine which factors are most dominant in the work area Community Health Center Pakjo Palembang. Study This use Case Control Study design. The sample consists of from 62 mothers pregnant, shared to 31 cases Preeclampsia and 31 controls Non-Preeclampsia, taken from recorded data medical 2023–2024. Data analysis using the Chi-Square test For Bivariate and Binary Logistic Regression for multivariate. Analysis : There is significant relationship​ in a way statistics between Positive MAP ( p-value <0.001, OR= 6.597) and overweight / obese BMI ( p<0.001, OR=8381 ) with incident Preeclampsia . Analysis Multivariate : After controlled by MAP, only High BMI was proven become predictor significant independent ( p = 0.030 ). Pregnant women with a high BMI have 4 times more chance big experience Preeclampsia (OR = 4.848; 95% CI: 1.165–20.182). The MAP variable became No significant in the multivariate model (p = 0.234). High BMI (Obesity / Fat) is factor the most dominant risk and is predictor strong independence​ to incident Preeclampsia. It is recommended that the Community Health Center Pakjo prioritize intervention programs that focus on management weight and counseling nutrition from the pre-pregnancy period and early pregnancy as primary prevention efforts Preeclampsia.